Implementation of Outseal PLC with RS-485 as a Multi Node in Chicken Farming Using Raspberry Pi and Node RED - Hanif Nurahmat; Yoedo Ageng Suryo (Universitas Islam Raden Rahmat, Malang, 2025)
Chicken farming is one of the important sectors in meeting food needs, but still faces challenges related to the ideal quality of the chicken coop environment, especially high levels of ammonia gas (NH₃) and non-ideal temperatures. Ammonia levels that exceed the threshold can harm chicken health and reduce productivity and result in chicken death. RS-485 as an industry standard communication is used as a Multi Node implemented in the Outseal PLC as an automatic control in chicken farming. Node-RED, as a browser-based visual programming platform, makes it easy for users to create IoT applications, including monitoring and control systems. The use of the Outseal PLC is used to control ammonia gas levels (NH₃) below the permissible threshold of below 20 ppm and the cage temperature below 35℃. The reading of the LM 35 sensor with the Outseal PLC ladder has an error percentage of 1.71% and the reading of the MQ 135 ammonia gas sensor with the Outseal PLC ladder has an error percentage of 1.303%. Raspberry Pi and Node are used to display ammonia gas levels and temperature in chicken farming. By implementing PLC Outseal with RS-485 as a Multi Node in chicken farming using Raspberry Pi and Node RED, it is hoped that it can increase productivity and achieve maximum results from chicken farming.